Behavioral Consequences of Optimal Tax Structure – Empirical Analysis - Stanislav Klazar (European Financial and Accounting Journal, 2010)
The aim of the paper was to analyze some behavioral effects, especially the effect of “hidden” tax, the “preference of progressivity” effect and some kind of “preference of short period incidence” effects of citizen. The effects predict the citizens will prefer hidden taxes to direct levies. The behavioral experiments revealed that additional information concerning the “hidden” tax and tax progressivity influences the preferences of respondents. They started to prefer the different ways of financing the public goods, those more progressive. Effect of “hidden” tax substantially diminishes after the prompting of information concerning the true tax incidence of corporate income tax. At the beginning the corporate income tax was preferred all over the groups, but later it lost its dominance and the alternative personal income tax became the favorable way how to finance of public goods. It is evident the relevant information concerning the real tax incidence and the redistributional effects of particular tax measures can significantly change the citizens view how to construct the preferred tax mix. It might also affect the process of political negotiation and reasoning.
Keywords: C91; H21; H22; H23; 650; Hidden tax; Progressivity of tax; Tax credit; Tax deduction; Behavioral experiments; Experimental economics